Twice enslaved : liberty and justice for Henrietta Wood - Castrovilla, Selene, 1966- (Calkins Creek, 2026)
Henrietta Wood was born enslaved. As a teen she was ripped from her family and sold. Years later, a miracle happened, and she was given freedom papers. But Henrietta's freedom was short-lived. She was tricked back into enslavement and sent to a Mississippi cotton plantation. On June 19, 1865--Juneteenth--she was emancipated. Finally free for good, Henrietta Wood sued the man who had kidnapped her back into enslavement--and she won! Henrietta was one of the few people in United States history to ever receive a reparation payment for slavery. Twice Enslaved is a true story of cruelty, resilience, and ultimately triumph, told lyrically for middle-grade readers by Selene Castrovilla and illustrated in full color by artist Erin Robinson.